Performance of Indonesian Candlenut Oil in the International Markets of the United States, Singapore, and India - Putri, Trisna Wahyu Swasdiningrum; Anggrasari, Herdiana (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2025)
The purpose of this study is to measure and analyze the competitiveness of Indonesian candlenut oil exports in three major market countries (the United States, Singapore, and India) using a quantitative and comparative approach. The data used in this study are from 2016 to 2023. The time series data analysis methods used are Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Trade Balance Index (TBI). Based on the RCA index calculation, the average RCA value of Indonesian candlenut oil is above 1. This means that Indonesian candlenut oil has a comparative advantage in the United States, Singapore, and India markets. The average RSCA index calculation shows that Indonesian candlenut oil has optimal competitiveness in the Singapore and India markets. Meanwhile, in the United States market, Indonesian candlenut oil does not have a comparative advantage. The average TBI calculation indicates that Indonesian candlenut oil is a high export commodity in the United States and Singapore markets, while in the Indian market, Indonesian candlenut oil has an export specialization but is still in the growth stage. Potential markets such as India, Singapore, and the United States deserve further development to optimize export profits. Dissemination of technology to improve the quality of candlenut oil to higher grades is also necessary to compete with competing countries, thereby increasing candlenut oil exports.